'To romanticise or not to romanticise the local': local agency and peacebuilding in the Balkans. Issue 1 (2nd January 2021) - Džuverović, Nemanja
ABSTRACT: Over the last decade there has been increasing attention within peace and conflict studies on the so-called 'local turn' in peacebuilding where the role of local actors, their agency and their relationship to international actors is strongly emphasised. Still, even with widespread academic optimism about the emancipatory potential of the local, strong caveats of 'not romanticising the local' are constantly repeated. By looking at the Balkan countries and their traditional practices of peacebuilding, this article asks whether the local has the potential to be the empowering agent or if such expectations are much too ambitious, both at the academic and policy level. Drawing on the research findings which show the persistence of coercive and noncoercive local peacebuilding practices, the article poses the Paris question once again: should liberal peacebuilding be saved, and if so, where are the locals in this rescue attempt?